The Development of Digital Literacy in Academic Context in Indonesia: Literature Review Study - Nazaruddin Musa; Norsiah Abd Hamid; Mohd Sobhi Ishak (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Academics in Indonesia are currently entering an era of rapid-learning change, as experienced by academics worldwide. This change is closely related to information and communication technology, such as the Internet and increasingly digital electronic devices. That digital cycle had had a significant impact on learning and evaluation, which is drastically different from the capabilities of manual systems before the digital era came to serve users in the academic community. However, the ease of technology does bring not only good news but also this digital accompanies problems such as overload, harmful substance, network neglect, and slavery to the device itself. It is hoped that this literature review will empower academics, especially students, to use this technology for their learning goals. This literature review paper investigates the digital learning framework model in a national academic context after the main study series in the previous finding paper on the computerization skills of academics in Indonesia. Therefore, this insight will be useful contribution to Indonesian academic work environment. Keywords: Digital Literacy, Indonesian Academic, Higher Education, Learning Approach